Dietary flavonoid kaempferol reduces obesity-associated hypothalamic microglia activation and promotes body weight loss in mice with obesity. (2nd January 2023) - Romero-Juárez, Pedro A.; Visco, Diego Bulcão; Manhães-de-Castro, Raul; Urquiza-Martínez, Mercedes V.; Saavedra, Luis Miguel; González-Vargas, Mari C.; Mercado-Camargo, Rosalio; Aquino, Jailane de Souza; Toscano, Ana E.; Torner, Luz; Guzmán-Quevedo, Omar
ABSTRACT: Background: Obesity results from an unbalance in the ingested and burned calories. Energy balance (EB) is critically regulated by the hypothalamic arcuate nucleus (ARC) by promoting appetite or anorectic actions. Hypothalamic inflammation, driven by high activation of the microglia, has been reported as a key mechanism involved in the development of diet-induced obesity. Kaempferol (KF), a flavonoid-type polyphenol present in a large number of fruits and vegetables, was shown to regulate both energy metabolism and inflammation. Objectives: In this work, we studied the effects of both the central and peripheral treatment with KF on hypothalamic inflammation and EB regulation in mice with obesity. Methods: Obese adult mice were chronically (40 days) treated with KF (0.5 mg/kg/day, intraperitoneally). During the treatment, body weight, food intake (FI), feed efficiency (FE), glucose tolerance, and insulin sensitivity were determined. Analysis of microglia activation in the ARC of the hypothalamus at the end of the treatment was also performed. Body weight, FI, and FE changes were also evaluated in response to 5µg KF, centrally administrated. Results: Chronic administration of KF decreased ∼43% of the density, and ∼30% of the ratio, of activated microglia in the arcuate nucleus. These changes were accompanied by body weight loss, decreased FE, reduced fasting blood glucose, and a tendency to improve insulin sensitivity. Finally, acute central administration of KF reproduced the effects on EB triggered by peripheral administration. Conclusion: These findings suggest that KF might fight obesity by regulating central processes related to EB regulation and hypothalamic inflammation. GRAPHICAL ABSTRACT: UF0001